The graft versus leukemia effect: donor lymphocyte infusions and cellular therapy - Maurer, Katie; Antin, Joseph H. (Frontiers in Immunology, 2024)
Allogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative therapy for many hematologic malignancies as well as non-malignant conditions. Part of the curative basis underlying HSCT for hematologic malignancies relies upon induction of the graft versus leukemia (GVL) effect in which donor immune cells recognize and eliminate residual malignant cells within the recipient, thereby maintaining remission. GVL is a clinically evident phenomenon; however, specific cell types responsible for inducing this effect and molecular mechanisms involved remain largely undefined. One of the best examples of GVL is observed after donor lymphocyte infusions (DLI), an established therapy for relapsed disease or incipient/anticipated relapse. DLI involves infusion of peripheral blood lymphocytes from the original HSCT donor into the recipient. Sustained remission can be observed in 20-80% of patients treated with DLI depending upon the underlying disease and the intrinsic burden of targeted cells. In this review, we will discuss current knowledge about mechanisms of GVL after DLI, experimental strategies for augmenting GVL by manipulation of DLI (e.g. neoantigen vaccination, specific cell type selection/depletion) and research outlook for improving DLI and cellular immunotherapies for hematologic malignancies through better molecular definition of the GVL effect.